2007
DOI: 10.1002/jcp.21038
|View full text |Cite
|
Sign up to set email alerts
|

Methylselenol generated from selenomethionine by methioninase downregulates integrin expression and induces caspase‐mediated apoptosis of B16F10 melanoma cells

Abstract: Melanoma is a highly metastatic cancer resistant to current chemotherapeutic and radiotherapeutic approaches. Several studies have shown that interactions between cancer cells and the extracellular matrix (ECM) are critical for the survival and invasion of metastatic cancer cells. In this study, we examine the effects of methylselenol generated from selenomethionine (SeMet) by methioninase (METase) on cell proliferation, adhesion, and expression of integrins in murine melanoma B16F10 cells, which are metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…It also catalyzes the conversion of the prodrug selenomethionine (SeMet) to toxic methylselenol, α-ketobutyrate, and ammonia. Methylselenol has been shown to be 1000-fold more cytotoxic to various cancer cells than SeMet (9) and was found to induce apoptosis and cell cycle arrest in cancer cells (10)(11)(12). SeMet cannot be converted to methylselenol by mammalian cells and is relatively nontoxic (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It also catalyzes the conversion of the prodrug selenomethionine (SeMet) to toxic methylselenol, α-ketobutyrate, and ammonia. Methylselenol has been shown to be 1000-fold more cytotoxic to various cancer cells than SeMet (9) and was found to induce apoptosis and cell cycle arrest in cancer cells (10)(11)(12). SeMet cannot be converted to methylselenol by mammalian cells and is relatively nontoxic (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…1B and C). It has also been reported that high doses of selenium induce cell death in the B16F10 melanoma cells [20]. As shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, many studies have reported that selenium is a strong inducer of cell death in numerous cancer cells [18]. Moreover, some studies have observed that sodium selenite exhibits anti-cancer and anti-metastatic activity against melanoma cancer cells [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in colon cancer cells (HCT116) this compound provoked gene modulation [161] related to transcription factors. In melanoma the proposed mechanism involved methylselenol, a metabolite [162] generated from SeMet by methioninase. A combined treatment with methioninase provoked phosphorylation of focal adhesion kinase (FAK) and Akt and activation of p38, PKC-delta and NF-kappaB.…”
Section: Selenide Derivativesmentioning
confidence: 99%